1999
DOI: 10.1038/sj.bjp.0702375
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nicorandil as compared to mixtures of sodium nitroprusside and levcromakalim in isolated rat aorta

Abstract: 1 The contribution of the relaxant mechanisms of nicorandil (NIC) were analysed by comparing its eects with those of sodium nitroprusside (SNP), levcromakalim (LEM) and mixtures (1:10, 1:30 and 1:100) of SNP:LEM in isolated endothelium-denuded rat aorta. 2 In rings precontracted with KCl (25 mM), the relative inhibitory potency of the soluble guanylate cyclase inhibitor ODQ and the K ATP channel inhibitor glibenclamide (GLI) on SNP:LEM mixtures showed a good correlation with the relative proportion of SNP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The inhibition of smooth muscle relaxation in rat aorta from normotensive and hypertensive rats correlates with the blockade of cGMP accumulation, which indicates an important contribution of cGMP to the arterial relaxation evoked by [Ru(terpy)(bdq)NO] 3+ and SNP. The relevance of sGC activation to NO donor-induced relaxation was reported in other studies (Bonaventura et al, 2005;Soloviev et al, 2004;Keeble et al, 2001;Sathishkumar et al, 2005;Cogolludo et al, 1999;Tseng et al, 2000). In the present study, the inhibitory effect of ODQ on the relaxation induced by [Ru(terpy)(bdq)NO] 3+ was higher in hypertensive rat aorta, since the relaxation was almost blocked when compared to normotensive rats.…”
Section: Discussionmentioning
confidence: 69%
“…The inhibition of smooth muscle relaxation in rat aorta from normotensive and hypertensive rats correlates with the blockade of cGMP accumulation, which indicates an important contribution of cGMP to the arterial relaxation evoked by [Ru(terpy)(bdq)NO] 3+ and SNP. The relevance of sGC activation to NO donor-induced relaxation was reported in other studies (Bonaventura et al, 2005;Soloviev et al, 2004;Keeble et al, 2001;Sathishkumar et al, 2005;Cogolludo et al, 1999;Tseng et al, 2000). In the present study, the inhibitory effect of ODQ on the relaxation induced by [Ru(terpy)(bdq)NO] 3+ was higher in hypertensive rat aorta, since the relaxation was almost blocked when compared to normotensive rats.…”
Section: Discussionmentioning
confidence: 69%
“…In the present study, glibenclamide partly inhibited the relaxation of HSV induced by nicorandil at higher concentrations. Previously, Cogolludo et al 28 suggested that in rat aorta, the contribution of the K ATP channel opening to the vasorelaxation is more important at high concentrations of nicorandil. Also, this result is in agreement with those in human umbilical arteries 29 and rabbit femoral artery, 30 which demonstrates that glibenclamide partially antagonized the relaxation induced by nicorandil.…”
Section: Discussionmentioning
confidence: 98%
“…The relative contribution of these 2 mechanisms to nicorandil-induced relaxation varies depending on the experimental protocol and preparations studied. For example, in the femoral and pulmonary arteries and the aorta, the activation of guanylyl cyclase plays a major role [6,11,26,27], whereas nicorandil exerts its effects on the coronary circulation mainly as a K ATP channel opener [28]. On the other hand, in the mesenteric arteries, both mechanisms contribute to the relaxant effects of nicorandil [8,10,11].…”
Section: Discussionmentioning
confidence: 99%
“…It produces relaxation in various smooth muscle preparations through 2 main mechanisms: (1) an increase in membrane K + conductance through the opening of ATP-sensitive K + (K ATP ) channels, leading to hyperpolarization, and (2) release of nitric oxide (NO), leading to elevated cyclic guanosine monophosphate (cGMP) levels by stimulation of soluble guanylyl cyclase [3,4,5,6,7]. The relative contribution of these 2 mechanisms to nicorandil-induced relaxation depends on the tissue and experimental conditions [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%